Effects of combined neutral endopeptidase 24-11 and angiotensin-converting enzyme inhibition on femoral vascular conductance in streptozotocin-induced diabetic rats - Arbin, V (2000)
1. The successive effects of the angiotensin-converting enzyme inhibitor captopril (CAP, 2 mg kg(−1)+1 mg kg(−1) 30 min(−1) infusion) and the neutral endopeptidase 24-11 inhibitor retrothiorphan (RT, 25 mg kg(−1)+12.5 mg kg(−1) 30 min(−1) infusion) were studied on femoral vascular conductance (FVC) in streptozotocin-induced diabetic (STZ-SD) and control Sprague-Dawley (C-SD) rats. The role of the kinin-nitric oxide (NO) pathway was assessed by (1) using pre-treatments: a bradykinin (BK) B2 receptor antagonist (Hoe-140, 300 μg kg(−1)), a NO-synthase inhibitor (N(ω)-nitro-L-arginine methyl ester, L-NAME, 10 mg kg(−1)), a kininase I inhibitor (DL-2-mercaptomethyl-3-guanidinoethylthiopropanoic acid, MGTA, 10 mg kg(−1)+20 mg kg(−1) 20 min(−1) infusion) and (2) comparing the effects in STZ-induced diabetic (STZ-BN) and control Brown-Norway kininogen-deficient (C-BN) rats. 2. In C-SDs, CAP and CAP+RT increased FVC similarly. In STZ-SDs, FVC and FBF were decreased compared to C-SDs. CAP+RT increased them more effectively than CAP alone. 3. In both C-SDs and STZ-SDs, the femoral bed vasodilatation elicited by CAP was inhibited by Hoe-140 and L-NAME. The FVC increase elicited by CAP+RT was not significantly reduced by Hoe-140 but was inhibited by L-NAME and Hoe-140+MGTA. 4. In C-BNs, the vasodilatator responses to CAP and CAP+RT were abolished and highly reduced, respectively. In STZ-BNs, these responses were abolished. 5. These results show that in STZ-SDs, CAP+RT improve FBF and FVC more effectively than CAP alone. These effects are linked to an increased activation of the kinin-NO pathway. BK could lead to NO production by BK B2 receptor activation and another pathway in which kininase I may be involved.